Studies on the IR reflectance trends and energy storage potential of metal antimonide incorporated jarosite dark colorants: A waste to wealth strategy - V.G. Prabitha; M. Shyni Raphael; V.N. Sheemol (Sustainable Chemistry for Climate Action)
The mineral jarosite, which is a by-product of zinc industry, has been examined here for a variety of environmental applications. By adding spectrally selective metal antimonides, a range of dark-colored inorganic-organic hybrid systems were created, and their NIR reflectance, Total Solar Reflectance (TSR), and other photophysical characteristics were thoroughly assessed. The techniques of DLS, Powder XRD and SEM were used to further describe these hybrid systems. The Jarosite blended FeSb system (JBM 4) was found to have 54 % of the NIR reflectance capability among the hybrid colorants that were examined. Applications involving surface coatings for heat management have been found to benefit from these colorants. Furthermore, the energy storage performance of Ni and Fe-based Jarosite antimonides were conducted using cyclic voltammetry. The study showed the possibility for affordable energy storage technology solutions by bridging the gap between advanced material development and industrial waste management. A waste to wealth paradigm was developed as a result of the Jarosite investigation.